2021
DOI: 10.3390/cancers13020233
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Heterogeneity of High Grade Colorectal Adenocarcinoma

Abstract: High grade colorectal carcinomas (HG-CRCs), which comprise 15% of colorectal carcinomas, are underrepresented in reported molecular studies. Clinicopathological, immunohistochemical, and molecular features of 40 HG-CRCs are described. Moreover, glandular and solid areas of 25 tumors were separately analyzed. The expression of MLH1, PMS2, MSH2, MSH6, p53, E-cadherin, CDX2, CK20, CD8, PDL1, PAN-TRK, c-MET, SMARCB1, ARID1A, SMARCA2, and SMARCA4 was analyzed by immunohistochemistry. Promoter MLH1 methylation was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Clonal diversity was due to the accumulation of mutations in genes of diverse pathways, such as Notch and MMR pathways (28). Notch signaling can provide the first mechanistic example of altered glycosylation in tumor cells with MSI (29).…”
Section: Mismatch Repair Was Regulated By Rnps1 Knockdown Through Notch Signaling Pathway In Vivomentioning
confidence: 99%
“…Clonal diversity was due to the accumulation of mutations in genes of diverse pathways, such as Notch and MMR pathways (28). Notch signaling can provide the first mechanistic example of altered glycosylation in tumor cells with MSI (29).…”
Section: Mismatch Repair Was Regulated By Rnps1 Knockdown Through Notch Signaling Pathway In Vivomentioning
confidence: 99%
“…Hypermutation is a hallmark of CRC, although 20% of these mutations cause cancer and far fewer mutations are common in two or more tumors ( 6 ). Patients within a mutational group are even heterogeneous ( 93 ). For example, in patients with the KRAS mutation, those with the mutation in codon 13 (G13D) respond to the combination of chemotherapy and targeted therapy, while patients with the mutation in codon 12 (G12R) do not respond well ( 94 ).…”
Section: Crc Heterogeneity: a Challenge Of Immunotherapymentioning
confidence: 99%
“…Only a few studies have analysed MMR status and molecular characteristics in CRC. A recent study demonstrated that only MMR-proficient CRC that lacked evidence of differentiation totally lost E-cadherin expression (Perna et al, 2021). Such a phenomenon has also been demonstrated in gastric carcinomas with MLH1 hyper-methylation (Moghbeli et al, 2014).…”
Section: Mismatch Repair Proteinsmentioning
confidence: 85%